Spatiotemporal inequality and financial toxicity of leukemia in post-poverty China: a national analysis of 832 counties (2019–2024) - Li, Wenping; Lv, Zhiyu; Chen, Mengdi; Xia, Dong; Wang, Jiayue; Chen, Jiapeng; Zhang, Lulu (Frontiers in Public Health, 2025)
BackgroundLeukemia remains a critical public health challenge in China’s post-poverty regions, where high treatment costs perpetuate the “disease-poverty” trap. Despite nationwide efforts to improve healthcare access, the evolving spatiotemporal dynamics and economic burden of leukemia in these regions remain understudied.MethodsUsing population-based data from China’s Health Poverty Alleviation Platform (2019–2024), we analyzed 97,472 leukemia cases across 832 poverty-alleviated counties. Age/sex-standardized incidence and mortality rates were calculated using 2020 census data. Spatiotemporal trends were evaluated via Joinpoint regression, and spatial clustering was mapped through global/local Moran’s I and Getis-Ord Gi* analyses. The economic burden was assessed by Out-Of-Pocket (OOP) payment ratios and costs.ResultsLongitudinal analysis of 97,472 leukemia cases across 832 Chinese poverty-alleviated counties (2019–2024) revealed: (1) Significant reductions in age-standardized incidence (AAPC = −59.4%, p = 0.015) and mortality (AAPC = −67.5%, p = 0.012), with persistently higher male incidence (χ2 = 1554.4, p < 0.001); (2) Spatiotemporal transition from Northeast/Central clustering (Moran’s I > 0.38, p < 0.001; 2019–2021) to Western hotspot expansion (Getis-Ord Gi*, p < 0.001; 2022–2024), indicative of improved diagnostic coverage; (3) Severe financial toxicity in Eastern China (median OOP ratio = 39.7%, approaching WHO catastrophic thresholds) and high absolute OOP cost clustering in Central regions, driven by therapy costs and insurance fragmentation.ConclusionWhile China’s poverty alleviation policies effectively reduced the leukemia burden, persistent regional disparities and financial toxicity demand targeted interventions. The westward hotspot migration post-2022 marks a diagnostic catch-up in resource-limited regions. Crucially, elevated male/youth incidence necessitates targeted screening in emerging clusters, while diverging financial toxicity demands region-specific solutions: for Eastern China’s catastrophic OOP ratios (39.7%), reform must prioritize novel-therapy reimbursement; Central China’s cost-clustering urges cross-provincial care networks to offset abandonment risks.